Validation of prognostic models: challenges and opportunities - Dijkland, Simone A.; Retel Helmrich, Isabel R. A.; Steyerberg, Ewout W. (Journal of Emergency and Critical Care Medicine; Vol 2 (November 2018): Journal of Emergency and Critical Care Medicine, 2018)
Multivariable prognostic models combine several characteristics to provide predictions for individual patients. Prognostic models can be applied in research and clinical practice, for instance to assist clinicians with decisions regarding treatment choices or informing patients and family members on prognosis (1).